2017
DOI: 10.1038/s41598-017-18156-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance exercise on endothelial progenitor cell mobilization in women

Abstract: This study aimed to determine the effect of a single bout of resistance exercise at different intensities on the mobilization of circulating EPCs over 24 hours in women. In addition, the angiogenic factors stromal cell-derived factor 1 (SDF-1α), vascular endothelial growth factor (VEGF), hypoxia-inducible factor 1-alpha (HIF-1α) and erythropoietin (EPO) were measured as potential mechanisms for exercise-induced EPCs mobilization. Thirty-eight women performed a resistance exercise session at an intensity of 60%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 45 publications
3
55
1
2
Order By: Relevance
“…A subsequent study found that a bout of intense exercise was associated with a release of CD34 + /KDR + endothelial progenitor cells from the bone marrow and that this effect was enhanced in individuals with elevated LDL/HDL and LDL/TC profiles ( 107 ). Likewise, a significant increase in the number of circulating EPCs, associated with increased levels of VEGF, HIF-1α, and EPO was found within hours after varying intensities of resistance training in women ( 108 ). Nonetheless, the physiological significance of these responses remains unclear, as the effects of exercise on angiogenesis and the wound healing response have not been systematically studied.…”
Section: Blood and Vasculaturementioning
confidence: 99%
“…A subsequent study found that a bout of intense exercise was associated with a release of CD34 + /KDR + endothelial progenitor cells from the bone marrow and that this effect was enhanced in individuals with elevated LDL/HDL and LDL/TC profiles ( 107 ). Likewise, a significant increase in the number of circulating EPCs, associated with increased levels of VEGF, HIF-1α, and EPO was found within hours after varying intensities of resistance training in women ( 108 ). Nonetheless, the physiological significance of these responses remains unclear, as the effects of exercise on angiogenesis and the wound healing response have not been systematically studied.…”
Section: Blood and Vasculaturementioning
confidence: 99%
“…Previous studies have demonstrated that exercise or physical activity could increase the level of HIF in skeletal muscle, which is involved in the angiogenesis process [8082]. Ribeiro et al showed that a bout of resistance exercise promotes the increases in EPCs and the expression of angiogenic genes such as VEGF and HIF1 α [80].…”
Section: Factors Induced By Exercise Regulate Bone Angiogenesismentioning
confidence: 99%
“…Even single exercise sessions, which increases the production of endogenous opioids (Geneen et al, 2017), angiogenesis factors (such as vascular endothelial growth factor [VEGF], hypoxia-induced 1 alpha factor [HIF-1α] and erythropoietin [EPO]) (Ribeiro et al, 2017) appear to be healthy, and they protect against hyperglycemia peaks (Lang Lehrskov et al, 2018) in humans. A single exercise session increases the plasma endocannabinoid levels in mice (Fuss et al, 2015), which is a possible mechanism for the euphoric state (runner’s high) that occurs after long runs (Boecker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%